Analysis of the operation of a microgrid with renewable distributed generation - Leite, V. (2018)
This article reports the ongoing research on the performance assessment of an experimental microgrid which integrates various renewable energy sources. The microgrid is based on a modular commercial solution, up to a rated power of 5 kW, integrating storage devices, a backup diesel generator and various renewable energy sources and also distributed energy sources developed under ongoing R&D projects, such as the integration of a pico hydropower plant with an interface able to perform power factor compensation of the microgrid, which is introduced briefly. The performance assessment of this microgrid is conducted through a characterization of different operational states and also a preliminary energy balance of the microgrid during a time span of 4 days.